Aromatherapy Improves Olfactory Acuity and Sexual Dysfunction in Postmenopausal Women - Deenadayalan Boopalan; Vijayakumar Venugopal; Poornima Ravi; Maheshkumar Kuppusamy (Tehran University of Medical Sciences, 2023)
No Abstract